Multidrug-resistant Escherichia coli carriage and associated risk factors among healthy individuals in Rural Southwestern Nigeria - Babatunde, Odetoyin; Oluwatoyin, Akinde (International Journal of Public Health Science (IJPHS), 2025)
Antimicrobial resistance (AMR), driven by multidrug-resistant (MDR) Escherichia coli, poses a significant public health threat, silently spreading through asymptomatic carriers. Limited data from rural areas highlight the need for focused studies to guide resistance control efforts. This study aimed to isolate faecal Escherichia coli (E. coli) from apparently healthy individuals in a rural community in Southwestern Nigeria, determine their antimicrobial resistance profiles, and evaluate risk factors associated with MDR E. coli carriage. A total of 347 stool samples were collected from healthy, consenting individuals. E. coli was isolated and identified using standard microbiological techniques. Antimicrobial resistance was assessed via the Kirby-Bauer disc diffusion method. Isolates were screened phenotypically for the extended spectrum beta-lactamase (ESBL) production and genotypically for ESBL genes (CTX-M, SHV, TEM). The data were analyzed using WINPEPI. E. coli was isolated from 269 participants (77.5%), yielding 555 isolates. High resistance rates were observed against sulphamethoxazole (94.0%), ampicillin (85.0%), and tetracycline (83.2%), while imipenem showed the lowest resistance (6.7%). Twenty-seven isolates (5%) were confirmed as ESBL producers. Among these, 17 (63%) carried at least one ESBL gene-TEM being the most common (44.4%). Additionally, 50.1% of the isolates were classified as MDR, with MDR E. coli carriage significantly associated with self-medication (p=0.05). The widespread presence of MDR E. coli among healthy rural dwellers, coupled with its association with self-medication, highlights serious public health concerns and raises the urgent need for more evidence-based strategies to combat AMR.